Transforming Educational Leadership: The Role of School Principals in Implementing Deep Learning-Based Curricula - Muh Faisal Halim (Journal of Educational Management Research, 2025)
Modern learning technology encourages the need for adaptive leadership in the school environment. This study aims to examine the role of the principal in implementing a Deep Learning-based curriculum, as well as the challenges and opportunities in resource management and teacher professional development. The research employs a qualitative case study approach, utilizing data collection techniques such as interviews, observations, and documentation. Data analysis will be carried out by condensing, reducing, displaying, and verifying data to identify key patterns related to leadership roles, challenges, and opportunities. The results reveal that the principal possesses a strategic vision of the importance of technology in education yet faces challenges such as general teacher training and limited funding. The implications of these findings highlight the need for more targeted and sustainable professional development programs and more effective resource management strategies to support the successful implementation of the Deep Learning curriculum. This study contributes to the literature on educational leadership and technology integration, offering recommendations for future research to explore these issues in broader school contexts, focusing on cross-regional or cross-level comparisons.